Impact of Celebrity Endorsed Advertisements on Rural Consumers’ Purchase Intention Towards Mobile SIM Cards : A Study Conducted in West Bengal - Chakraborty, Debarun (Indian Journal of Marketing, 2018)
Purpose : This study was conducted to find the impact of celebrity endorsed advertisements on rural consumers’ purchase intention towards SIM cards. Companies have tapped the rural market with the help of various strategies and have used celebrities to advertise their products in the market. There is a lack of empirical research on celebrity endorsements of telecom services in rural markets of India. Design/Methodology/Approach : I used descriptive research with cross-sectional design for this study. The study was conducted with multiple regression analysis to find out the results. Findings : The study revealed that familiarity was the most influencing factor under celebrity endorsements which had a significant and positive effect on purchase intention of SIM cards among rural consumers of West Bengal. The results also discovered that congruence did not have any impact on rural consumers’ purchase intention. Practical Implications : This study will be useful for telecom companies - who are operating in rural markets - to enhance their subscriber base. The study also revealed that celebrity endorsements in the rural market are quite profitable and the telecom companies can use celebrities to promote their brands. Originality/Value : The study was conducted in rural areas of West Bengal and the customers’ perceptions were gathered from the rural consumers only. In this domain, so far, no studies have been conducted in West Bengal.